2016
DOI: 10.20901/ms.7.14.9
|View full text |Cite
|
Sign up to set email alerts
|

Tweeting on Catalonia’s Independence: The Dynamics of Political Discussion and Group Polarisation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…On the one hand, diversification, polarisation, and commodification shaped the procés in online spaces (Balcells & Padró-Solanet, 2016). On the other hand, the institutional actors and ideologies described by previous studies on digital nationalism do not resemble the Catalan ones.…”
Section: Framing Digital Nationalism In Cataloniamentioning
confidence: 85%
“…On the one hand, diversification, polarisation, and commodification shaped the procés in online spaces (Balcells & Padró-Solanet, 2016). On the other hand, the institutional actors and ideologies described by previous studies on digital nationalism do not resemble the Catalan ones.…”
Section: Framing Digital Nationalism In Cataloniamentioning
confidence: 85%
“…First, as an open forum, it is evitable for people to encounter others holding opposite opinions [45]. In a study on conversational interactions about Catalonia's independence on Twitter, it is demonstrated that the conversations across political lines happen more frequently and last significantly longer than the homogenous ones [46]. Chan et al also verify that aggressive contents contributed by political opponents on social media can catalyze anger of the opponents and enhance conflicts.…”
Section: Descriptive Analysis Of the Articlesmentioning
confidence: 99%
“…Among the works analyzed for this study, the author finds no paper that specialized in studying subjective approaches, but this kind of approaches are frequently applied in most of the empirical works. Methods that are mentioned included scoring [28,52,73,74], Likert-type scales [27,75], coding [46,76,77], content analysis [78], and classification [79].…”
Section: How To Detect and Measure Opinion Polarization In Social Media?mentioning
confidence: 99%
“…GP occurs when group members end up being more extreme in their position on a given issue after participating or being exposed to a discussion [ 1 ]. The influential work of Cass Sunstein identified in online information cocoons created by like-minded individuals [ 2 – 4 ], i.e., a key mechanism of GP, and hypothesized that GP will impoverish public discourse and favor extremism [ 5 ]. How to effectively control the group polarization in emergencies is considered a vital topic for the management of online information disorder and public attitude guidance in emergency crises.…”
Section: Introductionmentioning
confidence: 99%